FEMALE PRAISE IN THE WORK OF POETS - Karimova S. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article analyzes the works of Erkin Vahidov about the external beauty of women. In the ghazals of Chustiy and Erkin Vahidov, thoughts about beauty are compared. The skill of the creators is evolved.